The effect of menstrual-cycle phase on immune responses to a 5-km cycling time trial: an exploratory study - Hicks, K. M.; Orange, S. T.; Dulson, D.; Ansdell, P.; Todryk, S.; Gilbert, S.; Saxton, J. M. (International Journal of Sports Physiology and Performance, 2023)
Purpose: Exercise has transient effects on the immune system that could influence infection risk and tissue recovery after exercise. Little is known about how the menstrual cycle interacts with the immune responses to acute exercise. This exploratory study sought to evaluate the effect of menstrual-cycle phase on peripheral blood mononuclear cell counts before and immediately after a bout of intense aerobic exercise. Methods: Seven naturally menstruating women (age: 27 [3] y) completed three 5-km cycling time trials coinciding with the early-follicular, late-follicular, and mid-luteal stage, confirmed by hormonal measurement. Venous blood samples were taken and examined for the presence of immune cell types using flow cytometry. Results: Reductions in circulating CCR7+ CD45RA+ naïve CD4+ T cells, CD4+ CD25+ regulatory T cells, and CD56+ CD57+ natural killer cells observed during the early-follicular phase were attenuated when exercise was performed during the late-follicular phase. Similarly, reductions in circulating CD56+ CD57+ natural killer cells and CD14+ TLR4+ monocytes following exercise in the early-follicular phase were abolished when exercise was performed in the midluteal phase. Conclusions: These preliminary findings indicate that the effect of acute high-intensity exercise on immune-cell mobilization and activation varies across the menstrual cycle, potentially impacting the anti-inflammatory effects of regulatory T cells and the cell-mediated effects of both natural killer CD57+ cells and monocytes expressing TLR4.